Assessment of physiological and quality traits of peace lily(Spathiphyllum wallisii) under coloured shade nets - Poojashree, N R; Suseela, T; Dorajee Rao, A V D; Subbaramamma, P; Sujatha, R V (Journal of Horticultural Sciences, 2025)
Studies were carried out to evaluate the physiological and quality traits of peace lily (Spathiphyllum wallisii) under different shade nets (50% shading) and control (tree shade). The results showed that plants grown under black-coloured shade nets recorded the maximum total chlorophyll content in leaves (79.02 SPAD units) and photosynthetic rate (1.64 μmol CO₂ m⁻² s⁻¹), while white shade nets promoted early flowering. The number of flowers produced per plant (2.00), flower stalk length (43.23 cm), flower stalk diameter (3.58 mm), spathe length (15.10 cm), spathe width (6.09 cm), and vase life (2.44 days) were highest in plants grown under black-coloured shade nets. Peace lily grown under black shade nets also showed overall better performance in root and foliage quality parameters; therefore, black shade nets can be recommended for commercial cultivation of peace lily.